Early Results of P Wave Regional Tomography Study at Sunda-Banda Arc using BMKG Seismic Network. Issue 1 (October 2021) - Haq, M S; Haolia,; Sulaiman, M I; Madrinovella, I; Satiawan, S; Zaky, D A; Suhardja, S K; Ramdhan, M; Priyono, A; Widiyantoro, S; Nugraha, A M S
Abstract: The plate movement, geological structure, magmatism, and seismic activity in the area of Bali to East Nusa Tenggara are mainly related with the subducting of Indo-Australian Plate underneath the Eurasian plate. The complexity is added with the recent collision of Australian continent lithosphere with the western Banda arc, along the islands of Flores, Sumba and Timor island. Our study area is known as the Sunda-Banda arc transition. With the aim of imaging subsurface structure, we perform seismic tomography inversion using regional events. We collected 5 years of earthquake data (January 2015 – December 2019) from the Indonesian Agency of Meteorology, Climatology, and Geophysics (BMKG). The output of our data processing is not limited to only P wave velocity model, but also relocated seismicity pattern in the region. In general, seismicity pattern shows dominant shallow events in the south that progressively shift into deeper events in the north down to a few 500 km, marking a dipping subduction zone in this region. A group of shallow events down to a depth of 50 km is also seen at the norther region that may relate to back-arc thrust activity. P wave tomogram model show a lower velocity perturbation at a depth of 30 km that could be associated with magmatic activity along the volcanic front line. Higher P wave perturbation model are spotted at two different zones, the first one is marking a dipping Indo-Australian plate down to depth of 400 km. We noticed that the angle of dipping is steeper in the Eastern part compared to the Western part. The second a relatively flat at shallow depth at the northern region from the island of Lombok to Nusa Tenggara Timur that may mark the back-arc thrust region